Temporal Dynamic Transcriptome Landscape Reveals Regulatory Network During the Early Differentiation of Female Strobilus Buds in Ginkgo biloba - Bai, Pan-Pan; Lin, Han-Yang; Sun, Yue; Wu, Jun-Jie; Gu, Kai-Jie; Zhao, Yun-Peng (Frontiers in Plant Science, 2022)
Flower bud differentiation is one of the most critical events for the reproductive success of seed plants. Yet, our understanding of genetic basis remains limited for the development of the reproductive organ of gymnosperms, namely unisexual strobilus or cone, leaving its regulatory network largely unknown for strobilus bud differentiation. Here, we analyzed the temporal dynamic landscapes of genes, long non-coding RNAs (lncRNAs) and microRNAs (miRNAs) during the early differentiation of female strobilus buds in Ginkgo biloba based on the whole transcriptome sequencing. Results suggested that the functions of three genes, i.e., Gb_19790 (GbFT), Gb_13989 (GinNdly) and Gb_16301 (AG), were conserved in both angiosperms and gymnosperms at the initial differentiation stage. The expression of genes, lncRNAs and miRNAs underwent substantial changes from the initial differentiation to the enlargement of ovule stalk primordia. Besides protein-coding genes, 364 lncRNAs and 21 miRNAs were determined functional. Moreover, a competing endogenous RNA (ceRNA) network comprising 1,196 lncRNA-miRNA-mRNA pairs was identified, which was highly correlated with the development of ovulate primordia. Using the living fossil ginkgo as the study system, the current study not only reveals the expression patterns of genes related to flowering, but also provides novel insights into the regulatory networks of lncRNAs and miRNAs, especially the ceRNA network, paving the way for future studies concerning the underlying regulation mechanisms of strobilus bud differentiation.